Electrochemical evaluation of stainless steel alloy as a ureteral stent in synthetic urine solution in-vitro with Candida urinary tract infection - Salma Mamdouh; Renad S. El-Kamel; Amany M. Fekry; Magda A. Ameer (BMC Chemistry)
Abstract This study evaluates the electrochemical performance of 316 L stainless steel alloy as a potential ureteral stent material in a synthetic urine environment mimicking conditions of Candida-associated urinary tract infections. The electrochemical behavior was investigated using electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and potentiodynamic polarization techniques, both in the presence and absence of Candida albicans. Results demonstrated that the formation of a biofilm by Candida albicans significantly influences the corrosion behavior of the alloy, as evidenced by changes in electrochemical parameters. Surface morphology and microbial adhesion were further confirmed through scanning electron microscopy (SEM), revealing biofilm development on the alloy’s surface. These findings highlight the critical role of fungal colonization in the degradation and stability of metallic ureteral stents under infection conditions.